印尼山口洋教师会华文师资的“在地化”培养模式研究 - Vivensius Thomas Tjhang (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2026)
This study found that the selection of “Xiaolaoshi” not only focuses on language proficiency but also emphasizes personal character, sense of responsibility, and teaching motivation. During the training process, schools use methods such as HSK examinations, class observations, and trial teaching to train or hone the teaching skills. The teaching ability of the “Xiaolaoshi” is evaluated through students’ academic performance, promotion rates, and feedback from students. In addition, challenges such as lack of experience, the dual pressure of studying and teaching, and salary issues are commonly faced by these “Xiaolaoshi”. In summary, the “Xiaolaoshi” training system in Singkawang provides valuable practical experience for promoting the development of Chinese language education.